2015
DOI: 10.1016/j.eswa.2014.09.061
|View full text |Cite
|
Sign up to set email alerts
|

A bipolar consensus approach for group decision making problems

Abstract: a b s t r a c tThis paper addresses the collaborative group decision making problems considering a consensus processes to achieve a common legitimate solution. The proposed resolution model is based on individual bipolar assessment. Each decision maker evaluates alternatives through selectability and rejectability measures which respectively represent the positive and negative aspects of alternatives considering objectives achievement. The impact of human behavior (influence, individualism, fear, caution, etc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 83 publications
(128 reference statements)
0
13
0
1
Order By: Relevance
“…In the current paper, BOCR (benefits, opportunities, costs and risks) analysis was used in combination with pairwise comparisons (Bouzarour-Amokrane, Tchangani, & Peres, 2015;Wijnmalen, 2007). The difference from the typical use of these analyses is that the model was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In the current paper, BOCR (benefits, opportunities, costs and risks) analysis was used in combination with pairwise comparisons (Bouzarour-Amokrane, Tchangani, & Peres, 2015;Wijnmalen, 2007). The difference from the typical use of these analyses is that the model was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Academically, many studies have been conducted on MCDM problems, and substantial progress has been made in this field. For example, Bouzarour-Amokrane et al formulated a consensus bipolar method to solve the collaborative group MCDM problems considering the impact of human behavior, e.g., individualism, fear, caution [42]. The analysis results of the application example about real size wind farm implantation problem showed that this proposed method can be a useful decision-making tool to solve this problem [42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Podemos mencionar casos de ejemplo en el sector productivo o dentro de la gestión de la cadena de suministro, en la selección de diversas estrategias [2][3][4][5][6], o hasta implementaciones en la solución a problemáticas sociales relacionadas con la salud, medio ambiente o políticas de responsabilidad social [7][8][9][10][11]. Otros autores han propuesto esquemas de consenso para juicios de expertos, que en su mayoría trabajan en sinergia con el Proceso de análisis jerárquico (AHP), así como la lógica difusa o el método TOPSIS [12][13][14][15][16][17][18], o bien con otras metodologías más particulares [19][20][21][22][23]. Del mismo modo, estudios anteriores de este tipo se enfocan en trabajos de investigación de revisión de literatura que giran en torno a estos modelos [24][25][26][27].…”
Section: Introductionunclassified